Implementation of a single quad MS detector in routine QC analysis of peptide drugs - Matthias D'Hondt; Bert Gevaert; Evelien Wynendaele; Bart De Spiegeleer (Elsevier, 2016)
A newly developed single quad mass spectrometry (MS) detector was coupled to a ultra-high performance liquid chromatography (UPLC) system and implemented in the routine quality control (QC) and impurity analysis of four therapeutic peptides, namely bleomycin sulfate, tyrothricin, vancomycin HCl and bacitracin, which were selected given their multi-component drug nature and their closely structurally related impurity profiles. The QC and impurity profiling results obtained using the ultra-high performance liquid chromatography ultraviolet/mass spectrometry (UPLC-UV/MS) detection system were analyzed against the results obtained using traditional high performance liquid chromatography-ultraviolet detection (HPLC-UV) methods derived from pharmacopoeial methods. In general, the used stationary phases of sub-2 µm particle (UPLC) technology resulted in lower limits of detection and higher resolution separations, which resulted in more detected impurities and shorter overall run times contrasting the traditional HPLC columns. Moreover, online coupling with a single quad MS detector allowed direct peak identification of the main compounds as well as small impurities, hereby increasing the information content without the need of reference standards.